THE INFLUENCE OF SERVICE QUALITY ON PUBLIC SATISFACTION AT THE AMUNTAI SELATAN SUB-DISTRICT OFFICE, HULU SUNGAI UTARA REGENCY. - Fatimah Fatimah; Jumaidi Jumaidi; Agus Surya Dharma (PPPM STIA Amuntai, 2026)
Services at the Amuntai Selatan District Office, Hulu Sungai Utara Regency are still faced with a number of obstacles, such as the uncertainty of service completion time, employee capabilities that are not fully in line with their duties and functions, and the low level of public satisfaction. Based on these conditions, this study was conducted to analyze the effect of service quality on public satisfaction. This study uses a quantitative approach with data collection techniques in the form of questionnaires, observation, and documentation. Based on calculations with the Slovin formula, the number of samples used was 56 respondents. Data processing and analysis were carried out through several stages, including validity tests, reliability tests, classical assumption tests, simple linear regression analysis, t-tests as hypothesis tests, and coefficient of determination tests, with the help of the IBM SPSS version 25 application. The results of the study prove that service quality has a significant influence on public satisfaction at the Amuntai Selatan District Office, Hulu Sungai Utara Regency. This is indicated by the regression equation Y = 4.923 + 0.678X, which means that every increase in service quality will increase public satisfaction by 0.678 or 68%. The calculated t-value of 12.422 is greater than the t-table value of 1.674 with a significance level of 0.000 (<0.05), so the alternative hypothesis is accepted. In addition, a correlation coefficient of 0.861 and a determination coefficient of 74% were obtained, indicating that the influence of service quality on public satisfaction is classified as very strong